Implementasi Penegakkan Hukum Tindak Pidana Pemilihan Umum Tahun 2024 oleh Sentra Penegakkan Hukum Terpadu (Gakkumdu) di Kota Padang - Syifana Azra; Adil Mubarak (AHKAM, 2025)
This research is motivated by the Integrated Law Enforcement Center (Gakkumdu), a forum that collaborates three institutions: the Election Supervisory Agency (Bawaslu), the Police, and the Prosecutor's Office (Kejaksaan Jaksa), to achieve a common understanding of law enforcement related to election crimes in Indonesia. However, in its policy implementation, problems remain related to the failure to optimally achieve the goals, functions, and essence of the Gakkumdu Center itself. The purpose of this study is to analysis the implementation of law enforcement for election crimes in 2024 by the Integrated Law Enforcement Center (Gakkumdu) in Padang City and to examine the factors influencing its implementation. The research method used is a qualitative approach with descriptive methods and data collection techniques, namely interviews and documentation. The theories used are policy implementation and the theory of factors influencing criminal law enforcement by Soerjono Soekanto in The results of this study indicate that the implementation of criminal law enforcement for the 2024 General Election by the Integrated Law Enforcement Center (Gakkumdu) in Padang City is still suboptimal. This is evident in the lack of human resources focused on their duties within the Padang City Gakkumdu, low accessibility, suboptimal coordination between Gakkumdu elements, unintegrated socialization and publication, and limited transparency. Furthermore, the implementation of this policy is influenced by legal factors, including regulatory dynamics, time constraints, and unclear interpretations of articles. Law enforcement factors indicate obstacles in coordination, legal understanding, and capacity to handle money politics. Facilities and infrastructure, although considered adequate, limited work space and supporting facilities reduce Gakkumdu's operational efficiency. Societal factors, such as low legal awareness and apathy toward election violations, hinder public participation in supporting law enforcement. Cultural factors, particularly economic conditions and vulnerability to money politics, reflect structural challenges that impact legal compliance.